Social networking sites, libraries, users - Hebrang Grgić, Ivana (2013)
In this paper, Facebook statistics will show the growth of the SNS. In short literature review published papers on using Facebook in libraries will be discussed. Results of a survey of students participants of 2012 Erasmus Intensive Program Library, Information and Cultural Management – Academic Summer School (IP Lib- CMASS) will be analyzed.
ENG